Target regulation of both VECs and VSMCs by dual‐loading miRNA‐126 and miRNA‐145 in the bilayered electrospun membrane for small‐diameter vascular regeneration. Issue 2 (21st November 2018) - Cui, Ce; Wen, Meiling; Zhou, Fang; Zhao, Yunhui; Yuan, Xiaoyan
Abstract: Clinical utility of small‐diameter vascular grafts is still challenging in blood vessel regeneration owing to thrombosis and intimal hyperplasia. To cope with the issues, modulation of gene expression via microRNAs (miRNAs) could be a feasible approach by rational regulating physiological activities of both vascular endothelial cells (VECs) and vascular smooth muscle cells (VSMCs). Our previous studies demonstrated that individually loaded miRNA‐126 (miR‐126) or miRNA‐145 (miR‐145) in the electrospun membranes showed the tendency to promote vascular regeneration. In this work, the bilayered electrospun graft in 1.5‐mm diameter was developed by emulsion electrospinning to dual‐load miR‐126 and miR‐145 for target regulation of both VECs and VSMCs, respectively. Accelerated release of miR‐126 was achieved by introducing poly(ethylene glycol) in the inner electrospun poly(ethylene glycol)‐ b ‐poly(l ‐lactide‐ co ‐caprolactone) ultrafine fibrous membrane, reaching 61.3 ± 1.2% of the cumulative release in the initial 10 days, whereas the outer electrospun poly(l ‐lactide‐ co ‐glycolide) membrane composed of microfibers fulfilled prolonged release of miR‐145 for about 56 days. In vivo tests suggested that dual‐loading with miR‐126 and miR‐145 in the bilayered electrospun membranes could modulate both VECs and VSMCs for rapid endothelialization and hyperplasia inhibition as well. It is reasonably expected that dual target‐delivery of miR‐126 and miR‐145 in the electrospun vascular grafts has effective potential for small‐diameter vascular regeneration. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 371–382, 2019.